Analysis of Polymorphisms rs7093069-IL-2RA, rs7138803-FAIM2, and rs1748033-PADI4 in the Group of Adolescents With Autoimmune Thyroid Diseases - Sawicka, Beata; Borysewicz-Sańczyk, Hanna; Wawrusiewicz-Kurylonek, Natalia; Aversa, Tommaso; Corica, Domenico; Gościk, Joanna; Krętowski, Adam; Waśniewska, Małgorzata; Bossowski, Artur (Frontiers in Endocrinology, 2020)
Graves’ disease and Hashimoto's thyroiditis are associated with a disturbance of immune tolerance of thyroid antigen molecules. The interleukin 2 receptor (IL2RA) is expressed by the regulatory T cells (Tregs) responsible for suppression. The FAIM2 encodes the molecule involved in the apoptosis inhibition process. The PADI4's expression is associated with activation of T-cells, differentiation of macrophages, which leads to increased inflammation. The aim of the study was to analyze the polymorphisms of the IL-2RA (rs7093069), FAIM2 (rs7138803) and PADI4 (rs1748033) genes and their correlation to thyroid hormones and anti-thyroid antibodies in pediatric patients with Graves’ disease and Hashimoto’s thyroiditis compared to the control group. The study was performed in 180 patients with GD, 80 with HT, and 114 children without any autoimmune diseases recruited from the endocrinology outpatient clinic. Three single nucleotide polymorphisms (SNPs): rs7138803-FAIM2, rs7093069-IL-2RA and rs1748033 PADI4 were determined. Rs7090369- IL-2RA allele T was more frequent in patients with AITDs (33.7% in GD vs 28.7% in HT, p=0.077, OR=1.52) compared with healthy children (25%). Allele T of that gene predisposes to the occurrence of autoimmune thyroid diseases, especially GD and TT genotype gives a statistically significant 5.2 times higher risk of GD (p=0.03, OR=5.26) and increased risk of HT (p=0.109, OR=4.46). Allele A rs7138803- FAIM2 is more frequent in patients with GD (p=0.071, OR=1.45) and HT (p=0.028, OR=1.8). In our data the presence of GG genotype of that gene significantly reduces the risk of autoimmune thyroid diseases (p=0.05, OR=0.42). The occurrence of CT genotype significantly reduces the risk of HT. 1.Polymorphisms rs7138803-FAIM2 and rs1748033-PADI4 are more frequent in patients with autoimmune thyroid diseases, more frequent in patients with Hashimoto’ thyroiditis, but the occurrence of GG rs7138803-FAIM2 genotype could reduce the risk of thyrocyte apoptosis inhibition. 2.The TT rs7093069- IL2RA genotype may increase the risk of autoimmune thyroid diseases. 3.Analysis of polymorphisms of given genes in clinical practice will allow to determine predisposition to autoimmune thyroid disease development, to find symptoms of thyroid gland dysfunction earlier and to use appropriate treatment.